2023
DOI: 10.3389/fnins.2023.1116154
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability during auricular acupressure at the left sympathetic point on healthy volunteers: a pilot study

Abstract: IntroductionThis research is a pilot, single-blinded study investigating heart rate variability (HRV) during auricular acupressure at the left sympathetic point (AH7) in healthy volunteers.MethodsThere were 120 healthy volunteers with hemodynamic indexes (heart rate, blood pressure) within normal ranges, randomly divided into two groups AG and SG (in each group having a gender ratio 1:1, aged 20−29), to receive either auricular acupressure using ear seed (AG) or sham method using adhesive patches without seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…A previous study investigating the effects of sympathetic nerve points revealed the activation of the parasympathetic nervous system, suggesting a positive effect on autonomic nervous system regulation. [ 53 ]…”
Section: Discussionmentioning
confidence: 99%
“…A previous study investigating the effects of sympathetic nerve points revealed the activation of the parasympathetic nervous system, suggesting a positive effect on autonomic nervous system regulation. [ 53 ]…”
Section: Discussionmentioning
confidence: 99%